The Interplay between Alexithymia and Insecure Attachment on Relationship Quality - Kordoutis, Panos; Moschos, Markos (Applied Family Therapy Journal (AFTJ), 2024)
Objective: Attachment insecurities along with emotional processing difficulties, pose important risks on romantic relationships. This study aims to investigate possible associations and the interplay of alexithymia and attachment orientation on relationship quality in romantic couples.Methods:  We used the actor–partner interdependence model and data from 56 heterosexual couples (N=112), who completed measures of attachment orientation, alexithymia and dyadic adjustment.Findings: Regression models indicated that both dimensions of attachment insecurity were associated with alexithymia and they consistently predicted lower relationship quality. Partner’s level of alexithymia moderated the relationship between attachment anxiety and dyadic adjustment. No significant interaction effects between attachment avoidance and alexithymia, were detected.Conclusion: The results point to the interdependent nature of emotional deficits and their effects on couple’s relationship quality. Theoretical implications and directions for future research are also discussed.